2022
DOI: 10.1007/s10823-022-09468-w
|View full text |Cite
|
Sign up to set email alerts
|

Caregiving Across International Borders: a Systematic Review of Literature on Transnational Carer-Employees

Abstract: In diaspora and transnational studies little is known about the experiences of transnational carer-employees (TCEs). TCEs provide unpaid/informal care across international borders to an adult family member, friend, or relative with disability and/or age-related needs, while also working in paid employment in the country of resettlement. The primary focus of this systematic review was to examine how cultural and historical elements of transnational caregiving influence the economic, social, and health/well-bein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 72 publications
0
7
0
Order By: Relevance
“…The experiences of this sample during the pandemic provide an in-depth description of the unique needs of this subpopulation and the barriers they face. Study findings can inform new and improved immigrant resettlement programs that specifically address transnational care, such as removing barriers to family reunification for parents/grandparents ( Sethi et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The experiences of this sample during the pandemic provide an in-depth description of the unique needs of this subpopulation and the barriers they face. Study findings can inform new and improved immigrant resettlement programs that specifically address transnational care, such as removing barriers to family reunification for parents/grandparents ( Sethi et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Caregiver-friendly workplace policies (CFWPs) could be implemented and/or adapted for TCEs, where “employers must be engaged in the conversations around the financial, emotional, and time investment required to maintain transnational communication” ( Sethi et al, 2022 , p. 454). CFWPs include flexible work options and tailored time off to accommodate geographical distances.…”
Section: Discussionmentioning
confidence: 99%
“…Eldercare is viewed as any assistance rendered to meet speci c physical, emotional, and nancial needs of older people. The literature has shown that geographic distance does not negate elder caregiving (Bei, Morrison, Zarzycki & Vilchinsky, 2023; Sethi, B., Williams & Leung, 2022). An extensive body of literature suggests that eldercare is underlined by cultural norms and values that shape attitudes toward older family members, which in turn in uence eldercare patterns.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Extended family-focused societies that emphasize family care for older adult members instils lial obligation and respect for older adults beginning in early childhood. Immigrants from such societies carry these family care values with them to their new destinations and feel obligated to care for their nonmigrant elderly relatives (Sethi et al, 2022;Gallois et al, 1999;Liu et al 2000). The lial obligation "forces" that engender eldercare by Ghanaian immigrants takes many forms and may include a combination of the following: concern over social and religious rewards and sanctions for eldercare; opportunities to show respect and gain respect from members of families and society; and feelings of obligation to provide family care (Kodwo-Nyameazea & Nguyen, 2008).…”
Section: Literature Reviewmentioning
confidence: 99%
“…A systematic review by Sethi et al [ 17 ] disclosed that due to the lack of CFWPs in the workforce along with geographical separation from their families, TCEs experience negative mental health impacts such as tension, guilt, shame, anxiety, and depression. Comparatively, a study by Amin and Ingman [ 2 ] assessed the emotional impact of providing transnational caregiving to elderly parents among TCEs living in the United States.…”
Section: Introductionmentioning
confidence: 99%